Naturally Occurring Functional Ingredient from Filamentous Thermophilic Cyanobacterium Leptolyngbya sp. KC45: Phytochemical Characterizations and Their Multiple Bioactivities - Kittiya Phinyo; Khomsan Ruangrit; Jeeraporn Pekkoh; Yingmanee Tragoolpua; Thida Kaewkod; Kritsana Duangjan; Chayakorn Pumas; Nakarin Suwannarach; Jaturong Kumla; Wasu Pathom-aree; Wenhui Gu; Guangce Wang; et al. (Antioxidants, 2022)
Cyanobacteria are rich in phytochemicals, which have beneficial impacts on the prevention of many diseases. This study aimed to comprehensively characterize phytochemicals and evaluate multifunctional bioactivities in the ethanolic extract of the cyanobacterium Leptolyngbya sp. KC45. Results found that the extract mainly contained chlorophylls, carotenoids, phenolics, and flavonoids. Through LC–ESI–QTOF–MS/MS analysis, 38 phenolic compounds with promising bioactivities were discovered, and a higher diversity of flavonoids was found among the phenolic compounds identified. The extract effectively absorbed the harmful UV rays and showed high antioxidant activity on DPPH, ABTS, and PFRAP. The extract yielded high-efficiency inhibitory effects on enzymes (tyrosinase, collagenase, ACE, and α-glucosidase) related to diseases. Interestingly, the extract showed a strong cytotoxic effect on cancer cells (skin A375, lung A549, and colon Caco-2), but had a much smaller effect on normal cells, indicating a satisfactory level of safety for the extract. More importantly, the combination of the DNA ladder assay and the TUNEL assay proved the appearance of DNA fragmentation in cancer cells after a 48 h treatment with the extract, confirming the apoptosis mechanisms. Our findings suggest that cyanobacterium extract could be potentially used as a functional ingredient for various industrial applications in foods, cosmetics, pharmaceuticals, and nutraceuticals.